Turystyka w planach strategicznych jednostek przestrzennych w warunkach zrównoważonego rozwoju - Nawrocka, Elżbieta (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The objective of the hereby article is to provide an answer to a question: whether and to what extent the development of tourism economy, according to the concept of sustainable development, is planned in the selected spatial units of Lower Silesia region. The diagnosis of documents of strategic significance and elaborated for the districts was applied. The group consisting of 12 out of 26 units of this type where tourism occupies a significant role in local economy was selected tor the study. The analysis and evaluation were performed based on the set of principles regarding sustainable tourism presented in the article. The research results pointed to the need of proper planning and monitoring of strategic concepts implementation, with particular emphasis on the assessment procedure of the influence of tourism development system on the broadly understood environment (applying measuring factors), the elaboration of information system about cultural, natural and social advantages, as well as the set of incentives stimulating for getting involved in pro-ecological economic activity in tourism. There also occurs the need to define local ecological attestations and the propagation of eco-labelling of tourist sectors. In all analyzed districts integrated planning of particular local economy sectors should be applied which also refers to tourism itself. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (7); 2007; nr 1185, s. 151-160